PROFILE ERYTHROCYTES OF Oreochromis niloticus FED WITH HERBS FERMENTED AND INFECTED WITH Aeromonas hydrophila - Nurfitri, Maya; Syawal, Henni; Lukistyowati, Iesje; Riauwaty, Morina (Asian Journal of Aquatic Sciences, 2023)
Herbs Fermented consist of Kaempferia galanga L, Curcuma xanthorrhiza Roxb, and Curcuma domestica Val, which are environmentally friendly disease prevention alternatives that can be added to feed because they have several advantages, such as increasing appetite, digestion, growth, disease resistance, and reducing stress levels in fish. This research was carried out from August to December 2021 at the Marine Science Biotechnology Laboratory and Fish Parasites and Diseases Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This study aimed to obtain the best dose from adding fermented herbs to increase the immune system of Oreochromis niloticus and prevent diseases caused by Aeromonas hydrophila bacteria in terms of profile erythrocytes. The method used was an experimental method using a Completely Randomized Design (CRD) with one factor, five levels of treatment, and three replications so that 15 experimental units were obtained. The challenge test was carried out on the 32nd day using A.hydrophila with a density of 108 CFU/mL. The best dose was found in P3 with a dose of 200 mL/kg of feed, which showed a total erythrocyte of 2.09x106 cells/mm3, hemoglobin level of 7.70 g/dL, hematocrit value of 37.70%, and a normal erythrocyte morphology. Water quality ranged from temperature 27-29oC, pH 6.9-7.2, DO 3.1-4.4 mg/L, and Ammonia 0.016-0.024 mg/L. Based on the data obtained, it can be concluded that fermented herbs can increase the immunity of O. niloticus to diseases caused by A.hydrophila.